Task flow in L2 writing: Antecedents and effects on task performance - Li, Chengchen; Dewaele, Jean-Marc; MacIntyre, Peter (Studies in Second Language Learning and Teaching, 2026)
Flow has been highly valued by educational researchers and practitioners for its positive effects on learner well-being, learning outcomes, and academic success. While interest in flow within second language (L2) acquisition has grown recently, comprehensive evidence remains limited regarding both its antecedents and its impact on L2 task performance, particularly in writing contexts. Grounded in Egbert’s (2003) theoretical model of flow and language acquisition, this study investigated how flow states in L2 writing are shaped by learners’ prior writing proficiency and immediate perceptions of task control, and how these factors collectively influence writing task performance. A total of 206 Chinese eighth-graders learning English as a foreign languagecompleted a pre-task L2 writing proficiency test, an argumentative writing task, and post-task scales measuring task flow and task control. Path analysis revealed that perceived task control predicted task performance both directly and indirectly through its influence on task flow. In contrast, L2 writing proficiency predicted task performance directly, without mediation by task flow. These findings largely support Egbert’s (2003) model within a task-based L2 writing context. The study suggests pedagogical implications for task design, emphasizing the importance of fostering a sense of control to facilitate flow states and enhance task performance.